2010
DOI: 10.1007/s11661-010-0517-7
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Microstructural Evolution and Dynamic Recrystallization During Isothermal Deformation of a Ti-Modified Austenitic Stainless Steel

Abstract: Dynamic recrystallization (DRX) behavior in hot deformed (by uniaxial compression in a thermomechanical simulator in the temperatures range 1173 K to 1373 K [900°C to 1100°C]) Ti-modified austenitic stainless steel was studied using electron back scatter diffraction. Grain orientation spread with a ''cut off'' of 1 deg was a suitable criterion to partition dynamically recrystallized grains from the deformed matrix. The extent of DRX increased with strain and temperature, and a completely DRX microstructure wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(55 citation statements)
references
References 34 publications
4
51
0
Order By: Relevance
“…This implies that the substructure is 'dynamic' and readapts continuously to the increasing strain. At a critical strain, and correspondingly at a value/ variation in driving force, dynamically recrystallized grains appear at the original grain boundaries, which results in the so-called 'necklace structure' 12,13 . With further deformation, more and more potential nuclei are activated and new recrystallized grains appear 14,15 .…”
Section: Characteristics Of Softening Flow Behavior Coupling With Drxmentioning
confidence: 99%
“…This implies that the substructure is 'dynamic' and readapts continuously to the increasing strain. At a critical strain, and correspondingly at a value/ variation in driving force, dynamically recrystallized grains appear at the original grain boundaries, which results in the so-called 'necklace structure' 12,13 . With further deformation, more and more potential nuclei are activated and new recrystallized grains appear 14,15 .…”
Section: Characteristics Of Softening Flow Behavior Coupling With Drxmentioning
confidence: 99%
“…It is observed that DRX grains nucleate along prior grain boundaries by bulging mechanism, and this is similar to the nucleation mechanism observed in uniaxial compression of the same alloy. [2] The microstructural evolution at 1273 K (1000°C) reveals that DRX is marginal at 0.4 strain. However, a rapid progress of DRX at higher strains is observed at this deformation temperature because higher deformation SUMANTRA increases the defect density resulting in increased mechanical instability (i.e., higher driving force) in the microstructure.…”
mentioning
confidence: 96%
“…In our recent study, microstructural evolution and DRX behavior in a Ti-modified austenitic stainless steel (referred to as alloy D9) during hot working was investigated over a range of temperature (1173 K to 1373 K [900°C to 1100°C]) and strain (0.2 to 0.8) at a strain rate 10 seconds À1 . [2] The nucleation of new DRX grains has been found to occur by bulging of the parent grain boundary. The processing parameters have been found to influence strongly the grain boundary character distribution and DRX in alloy D9.…”
mentioning
confidence: 99%
“…The flow behaviors are very complex during hot deformation, and the parameters of hot deformation, such as temperature and strain rate, affect the flow stress significantly. Therefore, the control of deformation parameters is critical in optimizing the final mechanical properties [16][17][18][19][20]. Figure 4 indicates the true representative stress-stain curves of the studied alloy under various deformation conditions.…”
Section: Dynamic Softening Behaviormentioning
confidence: 99%